In vitro antagonistic study of maize root colonizing fungal isolates against Fusarium moniliforme causing ear rot disease of maize - Parimal Mandal; Zerald Tiru; Monalisha Sarkar; Arka Pratim Chakroborty; Ayon Pal (Journal of Tropical Life Science, 2021)
In the present study, different root colonizing fungal isolates were isolated from the rhizospheric soil of maize growing areas of Uttar Dinajpur, West Bengal. All the isolates including test pathogen were identified from Indian Type Culture Collection, New Delhi. Plant growth promoting maize root colonizing fungal isolates- Penicillium pinophilum (ITC NO. 11,201.19), Trichoderma harzianum (ITC NO.11,203.19), Trichoderma asperellum (ITC NO. 11,209.19), Aspergillus niger (ITC NO. 11,204.19) and Penicillum purpurogenum (ITC NO. 11,207.19) exhibited antagonistic activities against F. moniliforme (ITC NO. 11,208.19) in vitro. Two antagonistic isolates of T. harzianum and eleven strains of T. asperellum showed antibiosis mechanism for antagonism against F. moniliforme with the range of Percent Inhibition of Radial Growth from 62.41% to 88.57%. Competitive mode of antagonism against test pathogen by the isolates of P. pinophilum, P. purpurogenum and six isolates of A. niger were found. Percent of inhibition of radial growth ranged from 57.14% to 91.42%.Â